Antifungal activity of Peperomia subspathulata Yunck against three phytopathogenic fungi: Aspergillus, Botrytis, and Penicillium species - Gutiérrez, Doris (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2024)
Peperomia subspathulata Yunck is an aromatic plant of the Piperaceae family. This species is native to Colombia and Ecuador. It is used in food preparation for its aroma and has been traditionally used to treat blows and wounds. The present study evaluated the essential oil and the ethanolic extract of aerial parts from P. subspathulata against Aspergillus sp., Botrytis sp., and Penicillium sp. The essential oil was obtained by hydrodistillation, and gas chromatography coupled with mass spectrometry analyzed its composition. The ethanolic extract was obtained by maceration with ethanol 96%. The antifungal activity tests were conducted in a potato dextrose agar medium which different concentration of essential oil and extract were added. The main components identified in the essential oil were safrole (44.3%), α-bisabolol (24.2%), myristicin (4.7%), trans-β-caryophyllene (3.0%), viridiflorene (30%), α-humulene (2.3%), trans-nerolidol (1.5%), linalool (1.1%), methyleugenol (1.1%) and cis-farnesene (1.0%). The total phenolic content of the ethanolic extract was determined by the Folin-Ciocalteu method (48.5±0.5 mg gallic acid equivalent GAE/g of extract). The ethanolic extract and the essential oil inhibited the growth of microorganisms. The essential oil was the most effective against Botrytis sp. (MIC=500 µg mL-1) and Aspergillus (MIC=1,000 µg mL-1).